1988
DOI: 10.1002/macp.1988.021890512
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance studies on bacterial copolyesters of 3‐hydroxybutyric acid and 3‐hydroxyvaleric acid

Abstract: Copolyesters of 3-hydroxybutyric acid (HB) and 3-hydroxyvaleric acid (HV), P(HB-co-HV), were isolated from Alculigenes eutrophus and characterized by solution NMR, solid-state I3C CP/MAS NMR, and differential scanning calorimetry. The I3C CP/MAS NMR analysis was compatible with that of a random copolyester of oxy-(1 -methyl-3-oxotrimethylene) (B) and oxy-(l-ethyl-3-oxotrimethylene) (V) units which adopts a regular conformation of a 2, -helix in the solid state throughout a wide range of compositions varying f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 11 publications
2
15
0
Order By: Relevance
“…For both samples, the slope was between 0.5 and 0.6, indicating a random coil conformation in chloroform. These results are consistent with the results of Miyaki et al, 17 who found that indices for molar mass dependence of intrinsic viscosity and radius of gyration of PHB approached the limits for random coil molecular conformation in chloroform, and with the NMR results of Doi et al, 29 who showed that PHA molecules are flexible chains in chloroform.…”
Section: Resultssupporting
confidence: 93%
“…For both samples, the slope was between 0.5 and 0.6, indicating a random coil conformation in chloroform. These results are consistent with the results of Miyaki et al, 17 who found that indices for molar mass dependence of intrinsic viscosity and radius of gyration of PHB approached the limits for random coil molecular conformation in chloroform, and with the NMR results of Doi et al, 29 who showed that PHA molecules are flexible chains in chloroform.…”
Section: Resultssupporting
confidence: 93%
“…Figure 1 shows the 500-MHz 'H NMR spectrum of PHB at 27 "C. The assignments of the signals have been reported. 15 The conformational structure around the CH,-CH bond in solution can be determined by the analysis of the methylene proton resonances. The methylene protons (HA, HB) spin-couple to the methine proton (Hx), forming an ABX-type three-spin system.…”
Section: Resultsmentioning
confidence: 99%
“…Culture condition and media: A. eutrophus was cultured in NR medium (polypeptone, 10 g/l; yeast extract, 10 g/l; beef extract 5 g/l; and ammonium sulfate 5 g/l, pH 7.0) (Sambrook et al, 1989) and E. coli strain was grown in LB medium (Doi et al, 1988). Liquid cultivation were carried out with shaking at 30 OC for A. eutrophus and 37 oC for E. coli.…”
Section: Methodsmentioning
confidence: 99%